NUCLEAR CAPABILITY IN THE ISRAELI SECURITY STRAT-EGY AND ITS REPERCUSSIONS ON THE COURSE OF THE PEACE PROCESS IN THE ARAB REGION (Al-Mukhtar Journal of Economic Sciences, 2024)
Israeli nuclear capability represents a major concern among the Arab countries، given the serious threat it represents to their national security، especially after the Arab countries felt the weakness of their position in the settlement negotiations in the face of the strong Israeli negotiating position based on the monopoly of nuclear weapons in the region، which led to Israeli intransigence.” It is unjustified by refusing to implement UN Security Council resolutions، and not respecting what was agreed upon in the settlement negotiations beginning with the Madrid Conference in 1991 until today، This is in order to impose a peace program in their favor and at the expense of the national interests of the Arab countries، and in light of the obstruction of the peace process and the weakness of the peaceful option of the Arab countries، they were forced to adopt the option of resistance and search for a strategic، or even traditional، deterrent through which they can create a regional balance that restores balance to their negotiating position in a way that enables them of reaching a just peace process.
Keywords: Israeli nuclear capability; Arab-Israeli settlement negotiations; Arab national security